1994
DOI: 10.1002/acp.2350080102
|View full text |Cite
|
Sign up to set email alerts
|

More motivational aspects of an imagery mnemonic

Abstract: Mnemonics research has focused on cognitive aspects of mnemonics. This study explored some motivational aspects of mnemonics-factors that can affect how much people might want to use mnemonics. It was hypothesized that using a mnemonic can make learning easier and more fun. College students used the rhyming peg mnemonic to learn 12 sayings (e.g. 'Curiosity killed the cat'). The students rated the task as being easier (lower difficulty and effort) than did control students who learned the sayings without the mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Lanham's (2006) statement about arts is of relevance: "Last century abounded in visual exhortation to consider letters as images rather than alphabetic code, to look at them rather than through them" (p. 93). Highbee (1994) states that imagery mnemonics improves the cognitive effectiveness of recall, accommodating motivational potential with easier and more enjoyable learning. Besides, the features of Turkish language made it possible to use extra analogies both visual and auditory (analogy between the third person in Turkish [O] and zero [0] and curly feature of S).…”
Section: Discussionmentioning
confidence: 99%
“…Lanham's (2006) statement about arts is of relevance: "Last century abounded in visual exhortation to consider letters as images rather than alphabetic code, to look at them rather than through them" (p. 93). Highbee (1994) states that imagery mnemonics improves the cognitive effectiveness of recall, accommodating motivational potential with easier and more enjoyable learning. Besides, the features of Turkish language made it possible to use extra analogies both visual and auditory (analogy between the third person in Turkish [O] and zero [0] and curly feature of S).…”
Section: Discussionmentioning
confidence: 99%
“…research findings "provide evidence that instruction involving the use of mnemonic devices does enhance a student's formal reasoning skills and that this has the potential for application of knowledge to more varied tasks" [4] p. 11. In addition, "the use of mnemonics with college age students might have enough potential for making learning easier and possibly more fun" [5].…”
Section: Global Journal Of Intellectual and Developmental Disabilitiesmentioning
confidence: 99%
“…Mnemonics are rightly considered to improve data acquisition and recall,5 to facilitate understanding,6 to improve motivation and enjoyment,7 while supplying integration, meaning and cues where none existed 3. The effectiveness of the Advanced Cardiac Life Support mnemonics ‘4Hs’ and 4Ts’ and ‘EMD aide’ have been compared in a randomised trial, which showed an advantage for the latter 2.…”
Section: Introductionmentioning
confidence: 99%